Mutual Fund Investment For Generation Z: Psychological Factors and The Influence Of Consumption Culture - Marjohan, Masno; Fadila, Syerlina; Mamis, Yonartilia (Indonesian Development of Economics and Administration Journal, 2025)
Generation Z, as a digital generation that grew up with technology and wide access to information, shows an increasing interest in the world of investment, including mutual funds. This study aims to analyze the psychological factors and culture of consumption that influence the interest and investment behavior of mutual funds in Generation Z. Using a quantitative approach through a survey of Gen Z respondents, this study explores the motivational factors, social influences, and risk perceptions that shape their investment decisions. The results show that psychological factors, such as the need for financial security in the future, play an important role in driving mutual fund investment interest. In addition, the consumption culture influenced by social media and digital trends also influences Gen Z’s preference for investment products that are easily accessible and flexible. This study concludes that to attract more investors from Gen Z, financial institutions need to consider aspects of digitalization and personalization of investment products, as well as improve education related to risk management. The findings are expected to serve as a reference for financial service providers in designing more effective marketing and education strategies for the younger generation segment.